Streamflow sensitivity analysis to climate change for a large water‐limited basin. Issue 4 (20th February 2013) - Liang, Liqiao; Liu, Qiang
Abstract Partitioning precipitation (P) between streamflow (Q) and actual evapotranspiration (Ea) on a basin scale is controlled by climate change in combination with catchment characteristics. Fu's formulation of the Budyko framework was used to estimate Q as a function of two meteorological variables, P and potential evaporation (Ep), and one adjustable parameter reflecting characteristics of catchment conditions (ω). Results show that ω reflects the impacts of catchment characteristics on the partitioning of P between Q and Ea for the different water yielding regions. As predicted, Q was more sensitive to P than to comparable changes in Ep for the whole of the Yellow River Basin (YRB), a water‐limited basin, while it was shown to be highly sensitive to changes in P, Ep, and ω in the low water yielding region (LWYR) of the basin, followed by YRB and the high water yielding region of the basin. The high sensitivity of Q to P, Ep, and ω in LWYR indicates that the management of catchments within these zones is critical to the management of overall basin flow, mitigating impacts of climate change on Q. The Budyko framework, incorporating the adjustable parameter ω, outlines interactions between Q, climate, and characteristics specific to different water yielding regions. It also provides a new approach in understanding hydrological process response to climate change. Due to the obscure physical attributes of ω, an explanation of the parameter using soil or vegetation characteristics will aid in the understanding of the eco‐hydrological behaviour of catchments and help to provide more detailed catchment management options for which to mitigate climate change with respect to concerns regarding agricultural water usage. Copyright © 2013 John Wiley & Sons, Ltd.